Gender, genetics, and analgesia: understanding the differences in response to pain relief - Packiasabapathy, Senthil (J Pain Res, 2018)
Genetic variations and gender contribute significantly to the large interpatient variations in opioid-related serious adverse effects and differences in pain relief with other analgesics. Opioids are the most commonly used analgesics to relieve moderate-to-severe postoperative pain. Narrow therapeutic index and unexplained large interpatient variations in opioid-related serious adverse effects and analgesia negatively affect optimal perioperative outcomes. In surgical, experimental, chronic, and neuropathic pain models, females have been reported to have more pain than males. This review focuses on literature evidence of differences in pain relief due to multiple genetic variations and gender of the patient.